Evaluating the Impact of Electronic Payment Systems on Service Delivery: A Case Study of Warri Refining Petroleum Company - Shehu, Abolore Kamaldeen; Bardi, Peter Chifum (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
This study assesses the impact of electronic payment systems on service delivery at Warri Refining Petroleum Company (WRPC). Using a survey research design, data were collected from 250 participants through structured questionnaires and analyzed with SPSS. The findings indicate that the adoption of e-payment systems has significantly improved service delivery by reducing transaction turnaround times, enhancing customer satisfaction, and minimizing the risks associated with physical cash handling. Key benefits include increased convenience, reduced waiting times, and overall cost savings. Despite some challenges such as frequent service issues and security concerns, the study demonstrates the substantial positive effects of e-payment systems. Also, further investment in technology and increased customer education to optimize the benefits of electronic payments in the oil and gas industry.